Lessons learned from the COVID-19 control strategy of the XXXII Tokyo Summer Olympics and the XXIV Beijing Winter Olympics - Zhang, Y.; Ai, J.; Bao, J.; Zhang, W. (Emerging Microbes & Infections, 2022)
Coronavirus disease 2019 (COVID-19) has caused more than 500 million infections and 6.2 million deaths globally, resulting in numerous sporting events being cancelled or postponed. Therefore, effective control strategies are urgently needed to prevent COVID-19 transmission at these local and global events. This article introduced the strategies utilized at the Tokyo and Beijing Olympics and proposed several measures for future reference.